Basigin Promotes Cardiac Fibrosis and Failure in Response to Chronic Pressure Overload in Mice. Issue 4 (April 2016) - Suzuki, Kota; Satoh, Kimio; Ikeda, Shohei; Sunamura, Shinichiro; Otsuki, Tomohiro; Satoh, Taijyu; Kikuchi, Nobuhiro; Omura, Junichi; Kurosawa, Ryo; Nogi, Masamichi; Numano, Kazuhiko; Sugimura, Koichiro; et al.
Abstract : Objective—: Basigin (Bsg) is a transmembrane glycoprotein that activates matrix metalloproteinases and promotes inflammation. However, the role of Bsg in the pathogenesis of cardiac hypertrophy and failure remains to be elucidated. We examined the role of Bsg in cardiac hypertrophy and failure in mice and humans. Approach and Results—: We performed transverse aortic constriction in Bsg +/– and in wild-type mice. Bsg +/– mice showed significantly less heart and lung weight and cardiac interstitial fibrosis compared with littermate controls after transverse aortic constriction. Both matrix metalloproteinase activities and oxidative stress in loaded left ventricle were significantly less in Bsg +/– mice compared with controls. Echocardiography showed that Bsg +/– mice showed less hypertrophy, less left ventricular dilatation, and preserved left ventricular fractional shortening compared with littermate controls after transverse aortic constriction. Consistently, Bsg +/– mice showed a significantly improved long-term survival after transverse aortic constriction compared with Bsg +/+ mice, regardless of the source of bone marrow ( Bsg +/+ or Bsg +/– ). Conversely, cardiac-specific Bsg-overexpressing mice showed significantly poor survival compared with littermate controls. Next, we isolated cardiac fibroblasts and examined their responses to angiotensin II or mechanical stretch. Both stimuli significantly increased Bsg expression, cytokines/chemokines secretion, and extracellular signal–regulated kinase/Akt/JNK activities in Bsg +/+ cardiac fibroblasts, all of which were significantly less in Bsg +/– cardiac fibroblasts. Consistently, extracellular and intracellular Bsg significantly promoted cardiac fibroblast proliferation. Finally, serum levels of Bsg were significantly elevated in patients with heart failure and predicted poor prognosis. Conclusions—: These results indicate the crucial roles of intracellular and extracellular Bsg in the pathogenesis of cardiac hypertrophy, fibrosis, and failure in mice and humans. Abstract : Supplemental Digital Content is available in the text.